Love, Respect, and Being Centered Upon: Loewald's Image of Development in Childhood and the Consulting Room. Issue 1 (1st January 2018) - Chodorow, Nancy J.
ABSTRACT: This contribution begins from two Loewaldian formulations: one, the patient becomes a centered unit by being centered upon by the analyst, and two, analytic neutrality and the analytic attitude begin from love and respect for the individual and individual development. Loewald elaborates these aspects of the analytic attitude, as he emphasizes affective as well as semantic uses of language and an attunement to the patient's particular developmental place and possibility for understanding. Loewald's developmental view of change in analysis ties him to Erikson and points the analyst to age and the life cycle. I describe some of the goals and challenges of working with older patients and bring in Settlage's writings on adult development and analysis in old age.